Raw data of the ASV titration and Zn uptake experiments from The effect of acidification on the bioavailability and electrochemical lability of zinc in seawater - Ja-Myung Kim; Oliver Baars; François M. M. Morel (2016)
A poorly studied but potentially important consequence of the CO 2 -induced acidification of the surface ocean is a possible change in the bioavailability of trace metals, which play a critical role in the productivity and population dynamics of marine ecosystems. We report laboratory and field experiments designed to compare quantitatively the effects of acidification on the bioavailability of Zn, a metal essential to the growth of phytoplankton and on the extent of its complexation by model and natural ligands. We observed a good correspondence between the effects of pH on the rate of Zn uptake by a model diatom and the chemical lability of Zn measured by anodic stripping voltammetry (ASV). In model laboratory systems, the chemical lability and the bioavailability of Zn could either increase or decrease at low pH depending on the mix of complexing ligands. In a sample of coastal surface water, we observed similar increases in the ASV-labile and bioavailable Zn concentrations upon acidification, a result contrary to previous observations. These results, which can likely be generalized to other bioactive trace metals, mutatis mutandis , demonstrate the intricacy of the effects of ocean acidification on the chemistry and the ecology of surface seawater.